2007
DOI: 10.1590/s0103-50532007000100020
|View full text |Cite
|
Sign up to set email alerts
|

Identification of impact aroma compounds in Eugenia uniflora L. (Brazilian Pitanga) leaf essential oil

Abstract: O óleo essencial das folhas de Eugenia uniflora L. (Myrtaceae) foi obtido a partir do arraste a vapor em aparelhagem de Clevenger e analisado por cromatografia gasosa acoplada à espectrometria de massas. As folhas foram colhidas e imediatamente extraídas durante cinco dias consecutivos, às 9 e 14h, não sendo observada variação significativa no rendimento dos óleos extraídos no período. Furanodieno e seu produto de rearranjo, furanoelemeno (ou curzereno, num total de 50,2%), β-elemeno (5,9%) e α-cadinol (4,7%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 9 publications
2
26
0
8
Order By: Relevance
“…The fragments were collected from 40 to 450 u. Identification of oil components was based on the Kovats index, comparison of their mass spectral fragmentation patterns with the Mass Spectra libraries (Wiley 139, 275 and 7 and Nist 127), published data (Weyerstahl et al, 1988;Henriques et al, 1993;Lima et al, 1993;Morais et al, 1996;Maia et al, 1999;Ogunwande et al, 2005;Melo et al, 2007;Costa et al, 2009Costa et al, , 2010Peixoto et al, 2010) and myrrh essential oil injection (Mölleken et al, 1988). The GC-MS quantification was obtained using the total ions chromatogram (TIC) and was expressed as an average of the data obtained for three samples of extracted leaf oil.…”
Section: Gas Chromatography Mass Spectrometry (Gc-ms) Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The fragments were collected from 40 to 450 u. Identification of oil components was based on the Kovats index, comparison of their mass spectral fragmentation patterns with the Mass Spectra libraries (Wiley 139, 275 and 7 and Nist 127), published data (Weyerstahl et al, 1988;Henriques et al, 1993;Lima et al, 1993;Morais et al, 1996;Maia et al, 1999;Ogunwande et al, 2005;Melo et al, 2007;Costa et al, 2009Costa et al, , 2010Peixoto et al, 2010) and myrrh essential oil injection (Mölleken et al, 1988). The GC-MS quantification was obtained using the total ions chromatogram (TIC) and was expressed as an average of the data obtained for three samples of extracted leaf oil.…”
Section: Gas Chromatography Mass Spectrometry (Gc-ms) Analysismentioning
confidence: 99%
“…Some authors have reported the same retention time for both components (Melo et al, 2007), while others reported differences (Morais et al, 1996;Mölleken et al, 1998;Baldovini et al, 2001;Baser et al, 2003;Bertoli et al, 2004;Oguwande et al, 2005;Yang et al, 2005Yang et al, , 2007Raj et al, 2008;Wong et al, 2009;Joshi et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Em folhas de E. uniflora, o composto furanodieno e seu produto de rearranjo, furanoelemeno ou curzereno (50,2%), ß-elemeno (5,9%) e a-cadinol (4,7%) foram os constituintes majoritários (MELO et al, 2007). Possivelmente o óleo essencial, pela forma de obtenção e por ser um produto concentrado, apresente maior diversidade e concentração de substâncias com ação elicitora.…”
Section: Resultados E Discussõesunclassified